2018
DOI: 10.3390/molecules23071566
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Antibacterial Nisin–Peptoid Hybrids Using Click Methodology

Abstract: Antimicrobial peptides and structurally related peptoids offer potential for the development of new antibiotics. However, progress has been hindered by challenges presented by poor in vivo stability (peptides) or lack of selectivity (peptoids). Herein, we have developed a process to prepare novel hybrid antibacterial agents that combine both linear peptoids (increased in vivo stability compared to peptides) and a nisin fragment (lipid II targeting domain). The hybrid nisin–peptoids prepared were shown to have … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Another factor to consider,e specially in the interesto fd evelopingm ore stable antibiotics based on the structureo f nisin, [28][29][30][31] is the effect of residue mutation within lantibiotic binding rings on either solutionc onformation or antibacterial activity.S ignificant efforts have been directed towards understanding the effects of dehydro residue replacement,a st hese residues contribute to the metabolic instability of these pep-tides, however no clear picture has yet emerged. Palmer et al have shown that substitution of Dha5 for Ala in nisin ring A leads to significant conformational change of the isolated ring A, [32] conversely,o ur NMR studies [25] comparingi solated ring A structures of nisina nd mutacin Iw ith saturated analogues of mutacin Ir ing Ai ndicated that the replacement of Dha5 by either Ser or Ala did not significantly affectt he overall conformation of the Leu4-Xaa5-Leu6 portion of ring A.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor to consider,e specially in the interesto fd evelopingm ore stable antibiotics based on the structureo f nisin, [28][29][30][31] is the effect of residue mutation within lantibiotic binding rings on either solutionc onformation or antibacterial activity.S ignificant efforts have been directed towards understanding the effects of dehydro residue replacement,a st hese residues contribute to the metabolic instability of these pep-tides, however no clear picture has yet emerged. Palmer et al have shown that substitution of Dha5 for Ala in nisin ring A leads to significant conformational change of the isolated ring A, [32] conversely,o ur NMR studies [25] comparingi solated ring A structures of nisina nd mutacin Iw ith saturated analogues of mutacin Ir ing Ai ndicated that the replacement of Dha5 by either Ser or Ala did not significantly affectt he overall conformation of the Leu4-Xaa5-Leu6 portion of ring A.…”
Section: Introductionmentioning
confidence: 99%
“…Another factor to consider, especially in the interest of developing more stable antibiotics based on the structure of nisin, is the effect of residue mutation within lantibiotic binding rings on either solution conformation or antibacterial activity. Significant efforts have been directed towards understanding the effects of dehydro residue replacement, as these residues contribute to the metabolic instability of these peptides, however no clear picture has yet emerged.…”
Section: Introductionmentioning
confidence: 99%
“…The copper(I)-catalyzed Huisgen cycloaddition reaction between azides and alkynes (also known as "click chemistry") is widely used to functionalize labeled proteins since it takes place under physiological conditions allowing full retention of the protein structure (Kolb et al, 2001). For example, click chemistry proved to be efficient in producing nisin-peptoid hybrids for therapeutic use (Bolt et al, 2018). Further, in vitro metathesis reaction confirmed the capability of the variants for post-biosynthetic modifications such as conjugation reactions with ligands, labels, or tags using bio-orthogonal chemistry.…”
Section: Recombinant Lanthipeptides Produced By Incorporating Non-canmentioning
confidence: 94%
“…This is achieved at least in part by increasing the molecule's resistance to proteases, as the triazole aligns with the biological targets through hydrogen bonding and dipole interactions (Ahmad Fuaad et al, 2013). Peptide coupling through click chemistry has been the subject of several studies toward the development of target-specific bacterial probes and expanding application possibilities of this method (Arnusch, 2008;Yoganathan et al, 2011;Oldach et al, 2012;Slootweg et al, 2013aSlootweg et al, , 2014Koopmans et al, 2015;Bolt et al, 2018). A prominent example of applying click chemistry to enhance lantibiotics, is that of coupling nisin AB to lipid moieties (Koopmans et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting hybrid molecules exhibited increased stability, as well as potent antimicrobial activity against drug-susceptible and -resistant strains of Gram-positive bacteria. In other studies, the lipid II-binding motif (rings AB) of nisin has been conjugated with various functional molecules (Arnusch, 2008;Koopmans et al, 2015;Bolt et al, 2018).…”
Section: Introductionmentioning
confidence: 99%